2020
DOI: 10.1021/acsanm.9b02275
|View full text |Cite
|
Sign up to set email alerts
|

Colorless Transparent Melamine–Formaldehyde Aerogels for Thermal Insulation

Abstract: Aerogels have many unique properties such as low density and low thermal conductivity, and, in particular, transparent silica aerogels are attractive for thermal insulating windows. Practical applications of silica aerogels, however, have been limited because of their low mechanical strength, and it is still challenging to synthesize transparent and mechanically strong aerogels. Here, we report colorless transparent melamine–formaldehyde (MF) aerogels prepared via a nonaqueous synthetic strategy. The obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 25 publications
0
31
0
Order By: Relevance
“…As commonly seen in blue-tinted and opaque aerogel specimens, pores greater than 20-25 nm in diameter cause larger haze at shorter wavelengths due to Rayleigh scattering. 9,[27][28][29]49 The TEOS1: MTES:0.5TMCS ambigel samples featured this phenomenon with decreasing transmittance and haze increasing to 4.1% at wavelengths approaching 400 nm, giving the samples a slightly blue tint. On the other hand, the TEOS1 and TEOS1:MTES ambigel samples displayed transmittance greater than 95% and haze below 3.1% and 2.0%, respectively, throughout the visible range.…”
Section: Decreased Light Scattering By Small Pores With Narrow Size Dmentioning
confidence: 89%
See 1 more Smart Citation
“…As commonly seen in blue-tinted and opaque aerogel specimens, pores greater than 20-25 nm in diameter cause larger haze at shorter wavelengths due to Rayleigh scattering. 9,[27][28][29]49 The TEOS1: MTES:0.5TMCS ambigel samples featured this phenomenon with decreasing transmittance and haze increasing to 4.1% at wavelengths approaching 400 nm, giving the samples a slightly blue tint. On the other hand, the TEOS1 and TEOS1:MTES ambigel samples displayed transmittance greater than 95% and haze below 3.1% and 2.0%, respectively, throughout the visible range.…”
Section: Decreased Light Scattering By Small Pores With Narrow Size Dmentioning
confidence: 89%
“…A number of aerogel studies have demonstrated low thermal conductivity but only in partially transparent monolithic aerogels. [27][28][29] Supercritically dried silica aerogels for solar thermal receivers exhibited transmittance >90%, but measured thermal conductivity was not reported. 7,30 Nanoparticle synthesis approaches seem to produce transparent monoliths with controlled pore size (<5 nm), but with porosities of ∼50%, low thermal conductivity is not expected.…”
Section: Discussion Pointsmentioning
confidence: 99%
“…In order to make the aerogel more robust, the inorganic/organic composite aerogels can be prepared by reinforcing the network skeleton structure of organic polymers using the micron or nano‐scale inorganic materials. These aerogels exhibit better strength and dimensional stability than the pure silicone aerogels, which can be used as ideal insulation, flame retardant, and shock‐absorbing material 28–30 . SiO 2 particles have been widely used in the fields of construction and engineering in recent years as a result of their advantages of controllability in size, large specific surface area, low thermal conductivity, and adsorption capacity.…”
Section: Introductionmentioning
confidence: 99%
“…These aerogels exhibit better strength and dimensional stability than the pure silicone aerogels, which can be used as ideal insulation, flame retardant, and shock-absorbing material. [28][29][30] SiO 2 particles have been widely used in the fields of construction and engineering in recent years as a result of their advantages of controllability in size, large specific surface area, low thermal conductivity, and adsorption capacity. There is a strong affinity between the functional groups of some biopolymer molecules and the surface of SiO 2 particles, which can be formed a plurality of cross-linking points to create a diversified gel network structure.…”
Section: Introductionmentioning
confidence: 99%
“…After gelation and aging at 40 °C and 60 °C, the obtained monolithic gel underwent hydrothermal aging at 120 °C for 24 h, washing by solvent exchange, and finally drying from n-hexane. We employed DMF, not water, as the main solvent because methylomelamine is highly soluble in DMF and a heterogeneous network tends to form in water 17 . In addition, we used a small amount of 60 wt% nitric acid as a reaction catalyst.…”
mentioning
confidence: 99%